Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Indomaret Mangga Dua Square - Ade Hikmah; Irwin Ananta Vidada (PT. Karya Inovatif Nusantara, 2025)
Indomaret is one of the largest retail companies in Indonesia. Indomaret is widespread in Indonesia and has developed rapidly, more specifically in the Jakarta area. The aim of this research is to find out whether price and service quality have a significant effect on customer satisfaction at Indomaret Mangga Dua Square, specifically at Mangga Dua Square Mall, North Jakarta. Customer satisfaction is one of the key factors in improving company quality. The method used was to use a questionnaire totaling 97 people for the October-January period using Lemeshow's theory. This research uses a quantitative approach. The data results and samples of this research were processed using SPSS 24 software with multiple linear regression analysis techniques which include instrument tests, partial and simultaneous hypothesis tests. The results of this research show a significant positive influence on Indomaret Mangga Dua Square. Partially or simultaneously, the influence of price and service quality on customer satisfaction has a very positive influence on customers at Indomaret Mangga Dua Square